THE NEW PARADIGM OF SURAH AL FATIHAH BASED ON THE KEY CONCEPTS OF SOCIAL INTERPRETATION OF DAWAM RAHARJO - Janah, Miftahul; Haerudin, Haerudin (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2021)
When interpreting the Qur'an, a mufassir needs a paradigm and a foundation as the procedures and stages that become his reference. This paper attempts to discuss the paradigm and concept of interpretation promoted by Dawam Rahardjo, namely al-FÄtiá¸¥ah as the Qur'an in a nutshell which is contained in the work of the Ensiklopedi Al-Quran: Tafsir Sosial Berdasarkan Konsep-Konsep Kunci. Two objectives in this study, first, the arguments that make al-FÄtiá¸¥ah a paradigm and the extent to which these arguments can be justified. Second, steps, systematics and forms of interpretation by positioning al-FÄtiá¸¥ah as a paradigm and its shortcomings in interpreting the Qur'an. This research is in the form of library research in the form of descriptive-analysis and uses content analysis as the analytical method used. This discussion concludes that there are two verses of the Qur'an, namely QS. Ali Imran (03): 07 and QS. al-Hijr (15): 87 as the basis and form three conceptual frameworks of al-FÄtiá¸¥ah as a paradigm of interpretation of the Qur'an, namely the term ummu al-kitab as the attribution of surah al-FÄtiá¸¥ah, the two ummu al-kitab referred to as muá¸¥kÄm and the last term al-sab'u al-maá¹¡Äni which is also understood as al-FÄtiá¸¥ah. The weakness in the argument that is built is in the redefinition of muá¸¥kÄm or mutasyabÄ«h which do not have clear standards and references. While the form of interpretation with this concept ends with a systematic form of thematic presentation with two steps or procedures, namely departing from the key terms in Surat al-FÄtiá¸¥ah (inductive) and starting from other than Surat al-FÄtiá¸¥ah then returning to Surat al-FÄtiá¸¥ah (deductive). The first procedure has difficulties in developing the -evolutionist dimension-, while the second procedure will be very subjective because of the difficulty of matching the interpreted verse with the terms in Surah al-FÄtiá¸¥ah.